2021
DOI: 10.1111/jcmm.16997
|View full text |Cite
|
Sign up to set email alerts
|

Systematic proteomics analysis of lysine acetylation reveals critical features of placental proteins in pregnant women with preeclampsia

Abstract: Preeclampsia (PE) is a dangerous hypertensive disorder that occurs during pregnancy. The specific aetiology and pathogenesis of PE have yet to be clarified. To better reveal the specific pathogenesis of PE, we characterized the proteome and acetyl proteome (acetylome) profile of placental tissue from PE and normal‐term pregnancy by label‐free quantification proteomics technology and PRM analysis. In this research, 373 differentially expressed proteins (DEPs) were identified by proteome analysis. Functional enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
(141 reference statements)
2
7
0
Order By: Relevance
“…GSEA results revealed that the complement and coagulation cascades pathway was up-regulated in the proteome and acetylome analyses of placental tissues for GDM and PE pregnant women. Many studies demonstrate the pathological effect of the complement and coagulation cascades pathway in GDM and PE [13,21,22]. The significantly regulated proteins present only in the GDM group were mainly enriched in the phospholipid metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GSEA results revealed that the complement and coagulation cascades pathway was up-regulated in the proteome and acetylome analyses of placental tissues for GDM and PE pregnant women. Many studies demonstrate the pathological effect of the complement and coagulation cascades pathway in GDM and PE [13,21,22]. The significantly regulated proteins present only in the GDM group were mainly enriched in the phospholipid metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…All pregnant women with GDM meet ADA diagnostic criteria [19]. Exclusion criteria for all pregnant women were consistent with our previous study [13]. The study was approved by the Medical Ethics Committee of Shenzhen People's Hospital, and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 , 24 For instance, Tang et al used label-free quantification proteomic technology to compare placental proteomes of normal-term pregnant women and PE patients, and found that DEPs were involved in multiple biological processes associated with immunity and angiogenesis. 25 In the present study, 2260 highly reliable proteins were identified in nine placental tissues, and 60 proteins were differentially expressed between PE and normal placentas. These altered proteins are mainly enriched in biological processes, such as platelet degranulation, cell migration and adhesion, blood coagulation, and redox process, which are essential for the development of placenta.…”
Section: Discussionmentioning
confidence: 52%